2009
DOI: 10.1007/s12573-010-0015-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age and hematocrit on the coagulation of blood

Abstract: To examine the effects of age, hematocrit and the daily variation in hematocrit on coagulation of blood, the time of onset of coagulation (Ti) of whole blood obtained from donors including normal subjects and patients was measured by means of a rheological technique. The Ti value of recalcified blood decreased with an increase in age, but in donors aged 65 years or more (the elderly), the Ti value was almost independent of age. The Ti value for blood obtained from the elderly was significantly lower at lower h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Recent studies have revealed that blood coagulation is HCT dependent in which patients with an abnormally lower HCT might interfere with the capability of blood coagulation for bleeding, and that with an abnormally higher HCT of the blood is more likely to be associated with the increasing risk with the formation of thrombosis or embolism. 36 Our results demonstrate that it is possible to recognize abnormality in the coagulation rate by OCT detection.…”
Section: Resultsmentioning
confidence: 53%
“…Recent studies have revealed that blood coagulation is HCT dependent in which patients with an abnormally lower HCT might interfere with the capability of blood coagulation for bleeding, and that with an abnormally higher HCT of the blood is more likely to be associated with the increasing risk with the formation of thrombosis or embolism. 36 Our results demonstrate that it is possible to recognize abnormality in the coagulation rate by OCT detection.…”
Section: Resultsmentioning
confidence: 53%
“…The Ti value for the type II group was somewhat smaller than that for the type I group. It has been reported that coagulation of blood occurs faster in the elderly than in young adults, although Ti values are dependent on individuals [7,14], and hematocrit [15]. It is known that an increase in the fibrinogen concentration often leads to enhanced erythrocyte sedimentation [16], and blood coagulation is also enhanced by an increase in fibrinogen concentration [17].…”
Section: Discussionmentioning
confidence: 99%
“…Dehydration may also be linked to hematocrit increase and to an increased risk of thrombogenesis [8].…”
Section: Physiology Including Response To Tissue Damagementioning
confidence: 99%